Correlation Between Vascular Endothelial Growth Factor and Long-Term Occurrence of HCV-Related Hepatocellular Carcinoma After Treatment with Direct-Acting Antivirals. (14th September 2021) - Ramadan, Haidi K.; Meghezel, El-Zahraa M.; Abdel-Malek, Mohammed O.; Askar, Ashraf A.; Hetta, Helal F.; Mahmoud, Amal A.; Abdel-Aal, Amal M.
Abstract: We aimed to evaluate the correlation between vascular endothelial growth factor (VEGF) and long-term occurrence of hepatocellular carcinoma after HCV treatment with direct-acting antivirals (DAAs) and the HCC stage. Two groups with HCV-related liver cirrhosis and HCC were included: group 1, HCC following DAAs; group 2, HCC did not receive DAAs. The serum level of VEGF and HCC staging was evaluated. The duration between DAAs and HCC was 21.81 ± 11.66 months. Portal vein thrombosis (PVT) was observed more in group 1 (31%). VEGF was relatively elevated in group 1 compared to group 2. HCC patients after DAAs, showed elevated VEGF with frequent PVT.